United States-Latin American Relations, 1850-1903 : Establishing a Relationship - Leonard, Thomas M., 1937- (Book collections on Project MUSE., 1999)
"During the second half of the 19th century several forces in the United States, Latin America, and Europe converged to set the stage for the establishment of a more permanent relationship between the United States and Latin America. The key factors - security, economics, and modernization - created both commonalities and conflicts between and among regions. In this volume, scholars examine not only the domestic but also the geopolitical forces that encouraged and guided development of diplomatic relations in this rapidly changing period."--Jacket.